2009
DOI: 10.1007/s11883-009-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt pathway: A macrophage effector molecule that triggers inflammation

Abstract: Wnt proteins are members of the highly conserved wingless family of proteins responsible for cell differentiation and development and for neoplastic and degenerative processes. Recently, Toll-like receptor-mediated Wnt signaling was found to be associated with innate immunity in Drosophila. Upregulation of Wnt5A in human macrophages upon microbial challenge indicated a similar mechanism. Toll-like receptor-mediated Wnt5A expression is a key process for sustained inflammatory macrophage activation through autoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 49 publications
5
84
0
1
Order By: Relevance
“…We found enrichment of differentially methylated promoters in the WNT signaling pathway complex with hypomethylation of 15 genes in the abused. Elsewhere this pathway complex has been found to play a key role in embryonic development and cellular proliferation [48], and is deregulated in some chronic health conditions such as obesity [49][50][51], diabetes [52][53][54], metabolic syndrome [55], cancer [56][57][58][59] and inflammatory processes [56][57][58]. Whilst recognizing that our findings do not provide evidence for causal links between child abuse and later outcomes, they nonetheless raise the prospect of mediation by epigenetic modifications.…”
Section: Discussionmentioning
confidence: 66%
“…We found enrichment of differentially methylated promoters in the WNT signaling pathway complex with hypomethylation of 15 genes in the abused. Elsewhere this pathway complex has been found to play a key role in embryonic development and cellular proliferation [48], and is deregulated in some chronic health conditions such as obesity [49][50][51], diabetes [52][53][54], metabolic syndrome [55], cancer [56][57][58][59] and inflammatory processes [56][57][58]. Whilst recognizing that our findings do not provide evidence for causal links between child abuse and later outcomes, they nonetheless raise the prospect of mediation by epigenetic modifications.…”
Section: Discussionmentioning
confidence: 66%
“…Wnt5a is also associated with macrophage inflammatory responses (35) and plaque instability (36). Thus, the increase in Wnt5a levels in advanced lesions could be an attempt to block intracellular cholesterol accumulation, and this might ultimately lead to the deleterious effect of calcifying the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum level of miR-29a for patients with active pulmonary TB versus healthy controls, with sensitivity of 83% and specificity of 80%, respectively. (12,22). A recent study showed that miR-29a was specifically upregulated after the mycobacterial infection of human macrophages (24).…”
Section: Vol 49 2011 Circulating Mirnas In Tuberculosis 4249mentioning
confidence: 99%